Pengaruh Profitabilitas, Kebijakan Deviden, dan Leverage terhadap Nilai Perusahaan (Sektor Energi yang Terdaftar dalam Bursa Efek Indonesia Tahun 2019-2022) - Endah Sri Wahyuni; Evantrius Situmorang (CV Edujavare Publishing, 2024)
This research aims to determine the influence of Profitability, Dividend Policy and Leverage on Company Value in Energy sector companies listed on the BEI in 2019-2022. In this research, 16 companies were selected using purposive sampling criteria with a total of 64 objects studied in energy sector manufacturing companies during the period 2019 to 2022. The research design in this research includes descriptive quantitative research, namely research that analyzes data in the form of numbers. The data used is secondary data in the form of financial reports obtained from the website www.idx.co.id using multiple linear regression analysis techniques. The results show that profitability has a significant influence on company value, dividend policy has a significant influence on company value, leverage has a significant influence on company value and profitability, dividend policy and leverage together have a significant influence on company value.